Challenges in estimating airfield pavement strength - Angeliki Armeni; Andreas Loizos (Transportation Engineering)
Τhe knowledge of the bearing capacity of airfield pavements consists a valuable information for airport authorities in terms of airport asset management. This information can be also used for reporting the load-bearing capacity of airfield pavements according to globally recognized systems, which provide a useful communication code between the involved parties. However, since a detailed technical evaluation for accurately assessing the bearing capacity of an airfield pavement may be not always feasible in practice, reporting through the newly introduced index denoted as (Pavement Classification Rating) PCR becomes a challenging task. On this basis historical data of the existing (Pavement Classification Number) PCN index already available to airport authorities may be also useful. Therefore, the present study aims to investigate the existence of any potential correlation between PCN and PCR that could provide an overview of the modified reported strength expressed through PCR, in order to optimize decision-making procedures. For this reason, the PCN and PCR indices for various flexible and rigid airfield pavement cross-sections are determined according to Federal Aviation Administration (FAA) procedures. The study demonstrates the benefits of developing a model, which can provide a useful tool for airport authorities in order to support decision-making planning optimization in terms of airport asset management.